Hubungan Hubungan kadar hematokrit dan trombosit dengan derajat keparahan pasien demam berdarah dengue di RSUD dr. Doris Sylvanus tahun 2020-2021Hematokrit dan Trombosit dengan Derajat Keparahan Pasien Demam Berdarah Dengue di RSUD dr. Doris Sylvanus Tahun 2020-2021 - Putri, Nur Aisyah Dwi; Shinta, Herlina Eka; Patricia, Tisha (Barigas: Jurnal Riset Mahasiswa, 2023)
Dengue Hemorrhagic Fever (DHF) is an infectious disease caused by the Dengue Virus (DENV), transmitted through the Aedes spp. Examination of hematocrit levels and platelet counts can support the diagnosis of DHF. Early detection is needed to predict the severity and determine the appropriate management of DHF, to reduce the mortality rate due to DHF. It was knowing the relationship between hematocrit and platelet levels with the severity of dengue hemorrhagic fever in RSUD dr. Doris Sylvanus 2020-2021. Analytical observational research with sampling technique using total sampling. The data of this study were taken from the medical records of patients diagnosed with DHF and then analyzed using the Rank Spearman correlation test. The sample in this study amounted to 52 patients. Patients' hematocrit levels were within normal limits in 19 male patients (36.6%) and 20 female patients (38%). The patient platelet count <100,000/mm3 was found in 32 patients (61.5%). The results of Spearman's Rank analysis between hematocrit and the severity of DHF were p = 0.072 and r = 0.252, while between the number of platelets and the severity of DHF were p = 0.581 and r = -0.078. There is no relationship between hematocrit and platelet levels and dengue hemorrhagic fever severity.